2001
DOI: 10.1144/gsl.sp.2001.187.01.15
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for seismogenic normal faults at shallow dips in continental rifts

Abstract: Several recent observations indicate that normal faulting earthquakes occasionally occur on faults dipping <35 ° , dips often considered shallow. Most of these occur in the Woodlark and Aegean rifts. These two rifts are found to generate significantly more earthquakes than others and are the most rapidly extending, and so display the widest variety of fault behaviour. Even within the Woodlark Rift system extension rates vary along strike, with the shallowest-dipping faults confined to the most rapidly rifting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 60 publications
0
45
0
Order By: Relevance
“…Note however that the upper crustal tectonic grain imposed by syn-rift normal faulting is only one component of a more complex structural network likely to affect the Torlesse terrane, and that fault orientation and dip at the depth of nucleation of the largest earthquakes (typically 10Á15 km) are unknown. The inherited extensional fabric may play a significant role if the syn-rift normal faults penetrate through the upper crustal seismogenic zone to mid-crustal levels (Abers 2001). All the inverted normal faults analysed in this study dip at high angles (65Á808) from the surface to c. 3 km b.s.l., but changes in dip with increasing depth and/ or merging of faults into deeper detachment horizons cannot be ruled out.…”
Section: Discussionmentioning
confidence: 79%
“…Note however that the upper crustal tectonic grain imposed by syn-rift normal faulting is only one component of a more complex structural network likely to affect the Torlesse terrane, and that fault orientation and dip at the depth of nucleation of the largest earthquakes (typically 10Á15 km) are unknown. The inherited extensional fabric may play a significant role if the syn-rift normal faults penetrate through the upper crustal seismogenic zone to mid-crustal levels (Abers 2001). All the inverted normal faults analysed in this study dip at high angles (65Á808) from the surface to c. 3 km b.s.l., but changes in dip with increasing depth and/ or merging of faults into deeper detachment horizons cannot be ruled out.…”
Section: Discussionmentioning
confidence: 79%
“…Seismic velocity measurements from the D'Entrecasteaux Islands reveal anomalously low‐density mantle supporting the thinned crust, a relationship that suggests that extension has taken place in both the crust and lithospheric mantle within the Woodlark Rift [ Abers et al ., ]. In addition, crustal extension is expressed by active normal faults within the Woodlark basin [ Abers , ] and by the exposure of the east‐west series of gneiss domes in the D'Entrecasteaux Islands [ Hill et al ., ; Little et al ., ].…”
Section: Geological Settingmentioning
confidence: 99%
“…The study of this active system yielded important information on the kinematic and geometric evolution of rift-related detachment systems. Abers et al (1997) demonstrated that earthquakes associated with normal faulting occurred at depths of less than 10 km in the brittle field in an area with a seismically well-imaged reflection dipping at only 25-30 (Abers 2001). This reflection was drilled recently during ODP Leg 180 where it crops out at the seafloor (Taylor et al 1999a).…”
Section: Strain Evolution During Late-stage Riftingmentioning
confidence: 99%
“…Compared to many fossil detachment faults observed on land, which have dip angles of less than 10, the normal fault in the Woodlark-D'Entrecasteaux rift is still relatively steep. Evidence of earthquakes along subhorizontal detachment faults (<10-15 dip) still has to be found (Abers 2001). In the following, I will describe two exposed subhorizontal (<15) detachment systems preserved in the Alps and one drilled and seismically imaged in Iberia.…”
Section: Strain Evolution During Late-stage Riftingmentioning
confidence: 99%